Performance of Lactate and CO2-Derived Parameters in Predicting Major Postoperative Complications After Cardiac Surgery With Cardiopulmonary Bypass: Protocol of a Diagnostic Accuracy Study - Zhou, Xiao-Fen; Yu, Rong-Guo; Chen, Qian; Xue, Yi-Min; Chen, Han (Frontiers in Cardiovascular Medicine, 2021)
Background: CO2-derived parameters are increasingly used to identify either low-flow status or anaerobic metabolism in shock resuscitation. However, the performance of CO2-derived parameters in cardiac surgical patients is poorly understood. The objective of this study is to compare the performance of lactate and CO¬2-derived parameters in predicting major postoperative complications after cardiac surgery with cardiopulmonary bypass. Methods: This is a prospective, single-center, diagnostic accuracy study. All patients who receive elective cardiac surgery involving cardiopulmonary bypass will be screened for study eligibility. Blood samples will be taken for the calculation of CO2-derived parameters, including the venous-arterial difference in CO2 partial pressure (PCO2 gap), venous-arterial difference in CO2 content to arterial-venous O2 content ratio (Cv-aCO2/Ca-vO2), and venous-arterial difference in CO2 partial pressure to arterial-venous O2 content ratio (Pv-aCO2/Ca-vO2) at ICU admission, and 3 h, 6 h and 12 h later. Baseline, perioperative data will be collected daily for seven days; patients will be followed up for 28 days to collect outcome data. The primary endpoint is the occurrence of major postoperative complications. Receiver-operating characteristics (ROC) curve analysis will be carried out to assess the predictive performance of lactate and CO2-derived parameters. The performance of the ROC curves will be compared. Discussion: The performance of lactate and CO¬2-derived parameters in predicting major postoperative complications will be investigated in the non-sepsis population, which has not been extensively investigated. Our study will compare the two surrogates of respiratory quotient directly, which is an important strength.